Paper based cell culture: Electrospin-coated paper as natural extracellular matrix inspired biopolymer scaffold / Ng Kelvin - Ng , Kelvin (2021)
Paper has recently found widespread applications in biomedical fields, especially as an alternative scaffolding material for cell culture, owing to its properties such as fibrous nature, porosity, and flexibility. However, paper on its own is not an optimal material for cell culture and modification is necessary for its scaffold application. The present study focuses on modification of filter paper through electrospin-coating and dip-coating with polycaprolactone (PCL), a promising biomaterial in tissue engineering. Morphological analysis, physical properties analysis, evaluation of cell viability, alkaline phosphatase (ALP) activity and live/dead assays were conducted to study the potential of the modified paper-based scaffold. The results were compared to filter paper (FP) and electrospun PCL (ES-PCL) as reference samples. The results indicate that electrospin-coating is a simple and efficient way of modifying FP. It not only improves the morphology of the deposited electrospun layer through reduction of fiber diameter by nearly 75%, but also greatly reduces the scaffold fabrication time compared to ES-PCL. The tensile properties of electrospin-coated filter paper (ES-PCL/FP) are significantly higher than other scaffolds, which indicates the synergistic effect of modifying FP with electrospin-coating method. Furthermore, the electrospin-coating of PCL on FP creates a bimodal scaffold that resembles the hierarchical structure of ECM, which could be beneficial toward improving biocompatibility. In vitro studies were conducted on these scaffolds, by using human fetal osteoblast (hFOB) and human adipose derived stem cells (ADMSC), to study the cellular interaction with these scaffolds in the aspect of proliferation, adhesion, and differentiation. The biochemical assays (Resazurin assay) conducted on hFOB and ADMSC show an up-regulated proliferation rate over the time points, ES-PCL/FP provides significantly higher readings compared to all other groups. The immunofluorescent stain results also show improved cell-distribution and cell-scaffold attachment all over the ES-PCL/FP. Medium sorption and retention capability of the scaffolds, and the effect towards cell proliferation, have also been highlighted in this study.